Natural Killer Cells 2017
DOI: 10.5772/intechopen.69684
|View full text |Cite
|
Sign up to set email alerts
|

Donor Natural Killer Cells and Their Therapeutic Potential in Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Natural killer (NK) cells were first identified and named for their "natural" cytotoxicity to reject bone-marrow allografts in lethally irradiated mice. Different from T cells, NK cells require no prior sensitization or immunization to lyse transformed or virally infected target cells and are non-major histocompatibility complex (MHC)-restricted. However, recent progress in understanding of NK cells biology has proved that NK cells share some similar characteristics with T cells. During development, NK cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 188 publications
(203 reference statements)
0
0
0
Order By: Relevance
“…CD56bright CD16+ NK cells are the first to populate the bone marrow after bonemarrow transplantation and might shape the donor-transplant immune interaction [142]. The initial observation that relapse rates for leukemia after bone marrow transplantation were higher if the donor was an identical twin suggested that alloreactive NK cells promote a graft-versus-leukemia (GvL) effect [143].…”
Section: Nk Cells In Cancermentioning
confidence: 99%
“…CD56bright CD16+ NK cells are the first to populate the bone marrow after bonemarrow transplantation and might shape the donor-transplant immune interaction [142]. The initial observation that relapse rates for leukemia after bone marrow transplantation were higher if the donor was an identical twin suggested that alloreactive NK cells promote a graft-versus-leukemia (GvL) effect [143].…”
Section: Nk Cells In Cancermentioning
confidence: 99%